Valoración del impacto que tienen las salvaguardias, enfocado al sector automotriz (ckd chevrolet) en Quito periodo 2015-2016 - Muñoz Muñoz, Diana Elizabeth (2017)
The safeguards in Ecuador affect the automotive industry especially the Chevrolet brand, which involves the social, economic and human resources directly and indirectly immersed in the automotive sector, damaging the productive matrix to which it belongs, however, these measures Are of emergency to protect the domestic industry of the country that is threatening to the increasing importation of this item, with temporary restrictions in industries that are not prepared to face this change. By imposing tariffs on imports, which are measures imposed by the country upon the entry of foreign goods, it has caused the auto parts acquired by the Chevrolet brand to assemble its vehicles to increase its price, so that the acquisition of new vehicles in the market of the city of Quito will be diminished in a considerable percentage affecting of directly way the automotive industry of this city.